1999
DOI: 10.1179/135100099101534792
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of 3,4-DHPEA-EA and protocatecuic acid: a comparative assessment with other olive oil biophenols

Abstract: Olive oil contains several phenolic compounds with antioxidant activity, whose levels depend strongly on the kind of cultivar grown, fruit ripening effects and the oil extraction process. Therefore, the beneficial effects exerted by olive oil consumption on the resistance of low density lipoproteins (LDLs) to oxidation depend not only on an increased intake of mono-unsaturated fatty acids (e.g. oleate) which are less prone to oxidation, but also phenolic antioxidants. The aim of this study was to analyze in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 30 publications
2
55
0
3
Order By: Relevance
“…33 Strong antioxidant activity of 3,4-dihydroxyphenylethanol-elenolic acid was also reported. 26 The higher concentration of the linked forms of hydroxytyrosol and tyrosol present in our OVP extract 7 may account for the effects shown by OVP as compared with the isolated compounds studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Strong antioxidant activity of 3,4-dihydroxyphenylethanol-elenolic acid was also reported. 26 The higher concentration of the linked forms of hydroxytyrosol and tyrosol present in our OVP extract 7 may account for the effects shown by OVP as compared with the isolated compounds studied.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Quiles et al 27 reported that olive oil phenolics showed the most significant antioxidative effects in the order of hydroxytyrosol > caffeic acid > tyrosol at 10-250 lM in PC3 human prostate cancer cell line. However, in our study, only hydroxytyrosol and pinoresinol showed significant anti-invasive effects at 25 lM, while at the lowest concentration tested (1.56 lM), pinoresinol showed the highest anti-invasive effects (65% of control).…”
Section: Discussionmentioning
confidence: 99%
“…Methyl protocatechuate (2) was prepared from protocatechuic acid by heating with methanol containing 10% hydrogen chloride. Butyl (4) and isopropyl (5) protocatechuates were prepared by heating of protocatechuic acid and corresponding alcohols with a catalytic amount of concentrated sulfuric acid. tert-Butyl protocatechuate (6) was prepared as follows.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Among them, protocatechuic acid (3,4-dihydroxybenzoic acid) and gallic acid (3,4,5-trihydroxybenzoic acid) are typical molecules which show potent antiradical activity. 1,2,[5][6][7][8]11) We have examined the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging reaction 12,13) of those acids and methyl esters and found that methyl protocatechuate and gallate were converted to their oxidative dimers with different connectivities during reaction in an aprotic solvent.…”
mentioning
confidence: 99%
“…Various compounds, such as phenolic acids, ferulic acid, vanillic acid and protocatechuic acid, phenolic acid ester (g-Oryzanol, and phytic acid and inositol were found from rice bran (8)(9)(10)(11). Phenolic acids act as an antioxidant (12)(13)(14)(15)(16), as a radical scavenger (13), as an inhibitor of hepatic cytochrome P450 (17), as an antibacterial agent (18) and also as an antiinflammatory agent (19,20). In our search for new naturally occurring antimutagenic compounds in plants, with a history of safe use as Chinese crude drugs (21,22), we found that the methanol extract of black rice bran exhibited a suppression of the furylfuramideinduced SOS response.…”
mentioning
confidence: 99%